2020
DOI: 10.16951/atauniiibd.701686
|View full text |Cite
|
Sign up to set email alerts
|

Kamu Harcamalarının Ekonomik Büyüme Üzerindeki Etkisi: Wagner Yasası’nın ve Keynesyen Hipotez’in Türkiye'de Geçerliliği Üzerine Bir İnceleme

Abstract: Bu çalışma, Türkiye'de 2006-2019 dönemi için kamu harcamalarının ekonomik büyüme üzerindeki rolünü ve Wagner Yasası ile Keynesyen Hipotezinin geçerliliğini incelemeyi amaçlamaktadır. Bu kapsamda çalışmada, üçer aylık zaman serileri kullanılmış olup Phillips-Ouliaris eşbütünleşme ve hata düzeltme modeli Granger Nedensellik test yöntemleri uygulanmıştır. Elde edilen bulgular, Türkiye'de 2006-2019 döneminde kamu harcamalarının reel gayrisafi yurtiçi hasıla büyümesi üzerinde etkili olduğunu, hem Wagner Yasası'nın … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
3
0
4
Order By: Relevance
“…Telatar and Terzi's study [35] on the relations between economic growth, population, and education found a negative causal relationship between economic growth and population and a positive causal relationship between the number of vocational high school graduates and economic growth. In this study, it has been determined that vocational education has a positive effect on economic growth by creating added value.…”
Section: Discussionmentioning
confidence: 95%
“…Telatar and Terzi's study [35] on the relations between economic growth, population, and education found a negative causal relationship between economic growth and population and a positive causal relationship between the number of vocational high school graduates and economic growth. In this study, it has been determined that vocational education has a positive effect on economic growth by creating added value.…”
Section: Discussionmentioning
confidence: 95%
“…(2021) diğer çalışmaların aksine Türkiye'de Keynesyen Hipotezi'nin geçerli olduğunu belirlemişlerdir. Üstelik Altunç (2011), Kanca (2011), Oktayer (2011), Yaraşır Tülümce ve Zeren (2017), Atgür (2020) ve Erer (2022) yaptıkları çalışmada Türkiye için hem Wagner Yasası'nın hem de Keynesyen Hipotezi'nin geçerli olduğunu tespit etmişlerdir. Ayrıca her iki görüşün de geçerli olmadığını, daha açık bir ifadeyle kamu harcamaları ve GSYH arasında herhangi bir istatistiksel ilişki bulunmadığını belirleyen çalışmalara da rastlanmıştır.…”
Section: Literatür Taramasıunclassified
“…In the studies that test Wagner's Law and Keynes Hypothesis together and use time series analysis techniques, Guder et al [60], Paul and Furahisha [14], Tulumce and Zeren [61], Sit and Karadag [15], Paparas et al [1], Yavuz and Doruk [16], Sedrakyan and Varela-Candamio [62], Atgur [63], Popescu and Diaconu [64] and Selvanathan et al [65]'s research findings show that both Wagner's Law and Keynes Hypothesis are valid. Bagdigen and Çetintas [66], Ulucak and Ulucak [67], Timur and Albayrak [68] and Mokoena vd.…”
Section: Selected Literaturementioning
confidence: 99%